2017
DOI: 10.1016/j.chembiol.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Paradoxical Activation of AMPK by the Kinase Inhibitors SU6656 and Sorafenib

Abstract: SummarySU6656, a Src kinase inhibitor, was reported to increase fat oxidation and reduce body weight in mice, with proposed mechanisms involving AMP-activated protein kinase (AMPK) activation via inhibition of phosphorylation of either LKB1 or AMPK by the Src kinase, Fyn. However, we report that AMPK activation by SU6656 is independent of Src kinases or tyrosine phosphorylation of LKB1 or AMPK and is not due to decreased cellular energy status or binding at the ADaM site on AMPK. SU6656 is a potent AMPK inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 55 publications
5
48
0
Order By: Relevance
“…Studies on hepatic lipogenesis have targeted nutrient-dependent activation of the AMPK-mTOR-SREBP1 pathway in hepatic de novo lipogenesis (32), and it is well documented that AMPK activation inhibits SREBP1 through mTOR (45). A previous study has reported that sorafenib could activate AMPK indirectly by inhibiting mitochondrial metabolism and increasing cellular AMP: ADP and ADP:ATP ratios (46). Consistent with those findings, we found that the AMPK-mTOR-SREBP1 pathway was activated by reduced ATP levels due to mitochondria damage by sorafenib, thus resulting in the decrease of SCD1 expression ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on hepatic lipogenesis have targeted nutrient-dependent activation of the AMPK-mTOR-SREBP1 pathway in hepatic de novo lipogenesis (32), and it is well documented that AMPK activation inhibits SREBP1 through mTOR (45). A previous study has reported that sorafenib could activate AMPK indirectly by inhibiting mitochondrial metabolism and increasing cellular AMP: ADP and ADP:ATP ratios (46). Consistent with those findings, we found that the AMPK-mTOR-SREBP1 pathway was activated by reduced ATP levels due to mitochondria damage by sorafenib, thus resulting in the decrease of SCD1 expression ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular energy status sensor AMPK has been thought to promote cell survival under energy stress . AMPK phosphorylation can be triggered by the excessive ATP consumption and suppressed ATP generation, so as to mediating intracellular energy stress response. In the condition of sorafenib treatment, AMPK has been revealed to be activated since the agent repressed mitochondrial respiration and consequently decreased ATP levels in cardiomyocytes, HCC cells, and breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Specifically, activation of AMPK plays a protective role against sorafenibinduced de-energization in hepatocholangiocarcinoma cells, revealing that AMPK depletion potentiated sorafenib treatment efficacy 31 and AMPK activation contributed to sorafenib resistance. It has been widely known that AMPK phosphorylation is mediated by LKB1 45 and Ca 2+ -activated kinase, CaMKK2. 49,50 Nevertheless, endogenous mechanism modulating AMPK activation in sorafenib resistance is poorly understood.…”
Section: F I G U R E 4 Knockdown Of Sesn2 Inhibited Activation Of Aktmentioning
confidence: 99%
“…In cholangiocytes, sorafenib‐induced cAMP/protein kinase A (PKA) ‐ dependent Raf/MEK/ERK signalling activation has been described . Hereby, sorafenib seems to activate AMPK indirectly by inhibiting mitochondrial metabolism and increasing cellular AMP : ADP and/or ADP : ATP ratios .…”
Section: Discussionmentioning
confidence: 99%